Digital Storytelling: Boosting Literacy Practices in Students at A1-Level - Pedro Alejandro González Mesa (HOW)
This article describes the implementation of digital storytelling in an English language class of eleventh graders at a private school in Mosquera, Colombia. It is a descriptive qualitative study, carried out for about six months by using digital tools to foster language production in the language learners. The implementation contained digital storytelling as a pedagogical strategy for developing the writing literacy practice. The personal stories and media literacy allowed the participants to combine both narratives and digital elements when writing in English in a collaborative work-group in which they co-constructed their stories. The data collected was analyzed by using ATLAS ti. Open questions looked for information about the writing process and the digital tools implemented when creating the stories. The findings revealed that the participants developed writing and speaking manners while assuming different roles. In addition, the digitalization of stories strengthened their multi-literacies. The participants’ recordings of their voices helped them improve their oral production without worrying about their classmates’ opinion. Finally, negotiation in the group roles, as writer, designer and media creator, played an important role when working in groups.